2016
DOI: 10.21037/mhealth.2016.08.01
|View full text |Cite
|
Sign up to set email alerts
|

A mobile diabetes management and educational system for type-2 diabetics in Saudi Arabia (SAED)

Abstract: The pilot study of the SAED system showed that a mobile health technology can significantly improve the HbA1C levels among Saudi diabetic and improve their disease management plans. The SAED system can also be an effective and low-cost solution in improving the quality of life of diabetic patients in the Kingdom considering the high level of prevalence and the increasing economic burden of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 7 publications
(7 reference statements)
1
36
0
Order By: Relevance
“…Miller et al used a machine learning approach to extract information from drug prescriptions from electronic health record (EHR) data and identify factors associated with patient care flow deviations [ 23 ]. Another DSS with care flow tools was presented in the work of Alotaibi et al [ 137 ]. This system focuses on the management of T2D patients using advanced features, such as computerized alerts and reminders.…”
Section: Resultsmentioning
confidence: 99%
“…Miller et al used a machine learning approach to extract information from drug prescriptions from electronic health record (EHR) data and identify factors associated with patient care flow deviations [ 23 ]. Another DSS with care flow tools was presented in the work of Alotaibi et al [ 137 ]. This system focuses on the management of T2D patients using advanced features, such as computerized alerts and reminders.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we cannot measure the usage of MPA by each patient. Most previous studies highlighted that self‐care activities, which contain diet and exercise patterns, and diabetes knowledge, as well as the clinical outcomes, were improved by mobile phone intervention. On the contrary, one study of type 1 diabetes patients found that there was no improvement in self‐efficacy and self‐care behavior, despite a significant decrease in HbA1c.…”
Section: Discussionmentioning
confidence: 99%
“…A mobile‐based diabetes management and education system SAED was developed in Saudi Arabia for managing patients with type 2 diabetes. SAED intervention was able to significantly decrease the HbA1c in the patients when compared to control group …”
mentioning
confidence: 87%
“…SAED intervention was able to significantly decrease the HbA1c in the patients when compared to control group. 12 The effective implementation of mHealth systems would require the availability of suitable devices and mobile networks for patients.…”
mentioning
confidence: 99%